Brain health considerations in the modern lacrosse athlete - Rock Vomer; Kenzie Johnston; Brian C. Lau; Jeff Bytomski (Elsevier, 2022)
Introduction: The annual incidence of sport-related concussion ranges from 1.6 to 3.8 million concussions per year representing a common injury in sports. Lacrosse is a rapidly growing sport for both men and women and these athletes are at risk for concussion. The mechanism of injury for concussion in the men's and women's game are different as are the rules and equipment requirements. Objectives: To report the epidemiology, pathophysiology, presentation, and management of sport-related concussion and to highlight recent rule changes for men's and woman's lacrosse in regards to concussion prevention. Methods: PubMed and Scopus databases were searched. All levels of evidence (I-IV) pertaining to concussions in men's and women's lacrosse players were analyzed and presented in this narrative review. Results: For all high school boys' sports, lacrosse ranks number 3 for sports with the highest prevalence of concussions. Concussions most frequently result from athlete-to-athlete contact which represents 66.4% of the recorded concussions. For all high school girls' sports, lacrosse ranks number 2 for sports with the highest prevalence of concussions. In women's lacrosse, stick or ball contact with the athlete's head is the most common mechanism of concussion, accounting for 72.7% of the recorded concussions. Conclusions: Both men's and women's lacrosse players are at risk for concussion, even though there are different mechanisms for this injury between the 2 games. Sports medicine providers should be knowledgeable on diagnosis, management and prevention when caring for lacrosse players. Protective equipment and rule changes are potential means to continue to protect these athletes and still need further investigation.